Developing an English Module using Canva for Vocational High School in the Nautical Fishing Vessel Department - Risa Isnaningsih; I Made Sujana; Agus Saputra; Boniesta Zulandha Melani (Jurnal Ilmiah Profesi Pendidikan, 2025)
Vocational high schools require ESP-based English learning materials, especially in the Nautical Fishing Vessel department. This research aims to develop a teaching module using Canva in the tenth grade, majoring in Nautical Fishing Vessel at SMKN 1 Keruak. This research uses the Research and Development (R&D) method, using the ADDIE model and the Genre Based Approach (GBA) learning model in its development. Observation, interview, documentation and questionnaire were used in data collection. Then, the data was analyzed quantitatively and qualitatively. The results of this research were as follows: The Canva teaching module in the Building Knowledge of the Field (BKOF) section displays two readings and one video of descriptive text to build students' knowledge regarding the text. The Modeling of the Text (MOT) section explains the description and social function, structure, and language features of descriptive text. Part Joint Construction of the Text (JCOT) presents the task of creating guided descriptive text and presenting the results in Canva presentation slides. Meanwhile, the Independent Construction of the Text (ICOT) section presents the task of creating descriptive text individually. This Canva teaching module can be declared valid and can be used without revision based on expert validation results with a score of 95,25%. This module is also categorized as excellent and good based on 90% of the teachers' opinions and 78,98% of students’ opinions on the English teaching module through Canva.